Coronavirus Disease 2019 Pandemic: Strengthening water, sanitation, and hygiene facilities for interrupting the chain of transmission - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Journal of the Scientific Society, 2021)
The coronavirus disease-2019 (COVID-19) pandemic has stretched the health system beyond their capacity & capability. The initial evidence has suggested that the infection is transmitted from one person to another through close contacts and droplets and thus the role of infection prevention strategies is extremely important. It has been advocated that frequent and proper maintenance of hand hygiene can prove to be the most effective strategy to prevent infection acquisition. However, in order to maintain hand hygiene, it is ideal to have access to safe water, sanitation and hygienic (WASH) facilities, as this will significantly reduce the risk of the transmission of infection between humans. Thus, all steps should be taken to ensure that improved WASH facilities and waste management provisions are available at home, education institutions, workplaces, community and health care establishment. In conclusion, the provision of standard WASH facilities in all the settings is critical to strengthen hand hygiene practices and thereby plays a significant role in reducing the risk of acquisition of infection and thus the caseload of COVID-19.